Quantification of nipple size and shape among an ethnically diverse sample of US women - Peter Wildfeuer; Alexis Alban; Bob Worrell; Shilo Ben Zeev; Judith Shamian; Mike Woolridge (Academia Medicine)
Research aim: to quantify nipple shapes and sizes in an ethnically diverse convenience sample of US women. A total of 510 women were recruited into this study—using an iPhone App, employing the ‘True Depth Scanning’ software, and scanning their torso from both the left and right aspect to secure an image of each breast. They provided 1,129 scans, of which 835 (74%) were submitted to a purpose-built algorithm which isolated the nipple-areola complex as a definable 3D cube, which was re-aligned to enable key parameters of nipple geometry to be measured. Viable data were secured from 78% of the scans undertaken, yielding 538 datasets from 329 participants. Outcome: This is the largest study undertaken with a non-clinical, ethnically diverse population of women, employing a novel scanning process and applying a novel purpose-built algorithm—with a view to characterizing the shape and size of the nipple-areola complex, by collecting normative data on nipple geometry.